Climate‐change impacts exacerbate conservation threats in island systems: New Zealand as a case study - Macinnis‐Ng, Cate; Mcintosh, Angus R; Monks, Joanne M; Waipara, Nick; White, Richard SA; Boudjelas, Souad; Clark, Charlie D; Clearwater, Michael J; Curran, Timothy J; Dickinson, Katharine JM; Nelson, Nicola; Perry, George LW; et al. (Frontiers in ecology and the environment, 2021)
Rapid advances in eradicating invasive species from islands are improving conservation outcomes in these biodiversity hotspots. However, recent conservation gains could be reversed not only by future invasions from non‐native species but also by future extinctions of native taxa, both of which may be facilitated by – or exacerbated by interactions among drivers of – global environmental change. We highlight relevant knowledge gaps that must be filled to reduce uncertainty about the ecological effects of future climate change. We use Aotearoa New Zealand as a case study of island ecosystems to demonstrate that in addition to sea‐level rise, most ecologically meaningful impacts of climate change on biodiversity responses are indirect and due to exacerbation of existing threats, including the impact of invasive species as well as the loss and fragmentation of habitat. We identify key topics where progress is needed to future‐proof conservation management for island ecosystems susceptible to the direct and indirect effects of climate change.